(untitled) (Journal of Asian Development Studies, 2023)
The study examines the association between inspirational leadership and project success, along with the role of empowerment and psychological ownership. The study is performed in the construction sector of Pakistan and projects under progress in Lahore, Faisalabad, and Multan. The study is questionnaire-based, and quantitative data analysis is performed. The questionnaires were distributed to the 250 employees who are genuinely engaged in projects, and data was collected from 215 employees. The regression analysis was performed to examine the impact of inspirational leadership on project success. The mediation and moderation analysis were used to explore the mediation effect of empowerment and the moderation effect of psychological ownership. The results found that inspirational leadership impacts the project’s success. Further, the results reveal that psychological empowerment mediates the relationship between inspirational leadership and project success. The moderation influence of psychological ownership is also explored significantly in this study. The study concluded that inspirational leadership promotes a sense of self-responsibility and empowers employees in decision-making.